MATH TEACHERS’ STRATEGIES IN DEVELOPING CLASSROOM ACTIVITIES: A CASE STUDY OF BILINGUAL PROGRAM AT JUNIOR HIGH SCHOOL IN YOGYAKARTA - Rr. Hasti Robiasih (PAROLE: Journal of Linguistics and Education, 2014)
The practice of bilingual program in educational system in Indonesia is to improve the quality of education in secondary school. The achievement of such objective could be observed from teacher-student classroom interaction. The present paper addresses the math teachers’ strategies and interaction types in structuring classroom activities and type of interaction using English in teaching Math at bilingual class on a private and public junior high school in Yogyakarta. Research findings show that due to mediocre level of English they employed several strategies such as maximizing the use of textbooks or students’ worksheet, maximizing individual work, using demonstration in presenting the topics, and performing translation. The interaction types are mostly in the form of telling and instructing.   Pelaksanaan program bilingual dalam system pendidikan di Indonesia adalah untuk meningkatakan kualitas pendidikan di tingkat sekolah menengah. Pencapaian tujuan tersebut dapat diamati dari interaksi guru dan siswa di kelas. Paper ini mengungkap strategi yang digunakan guru matematika dalam mengembangkan aktivitas pembelajaran dengan bahasa Inggris sebagai pengantar pada program bilingual di salah satu sekolah menengah pertama swasta dan negeri di Yogyakarta. Hasil penelitian menunjukan bahwa para guru matematika menggunakan beberapa strategi dalam berinteraksi dengan siswa, seperti memaksimalkan penggunaan buku teks atau lembar kerja siswa, memaksimalkan tugas individu, mendemonstrasikan materi yang diajarkan, dan menterjemahkan. Sebagai kompensasi atas keterbatasan penguasaan bahasa Inggris mereka, jenis interaksi yang digunakan adalah memberi instruksi dan informasi